Linguistic Analysis of Self-Narratives of Patients With Gambling Disorder. (December 2020) - Altavilla, Daniela; Acciai, Alessandro; Deriu, Valentina; Chiera, Alessandra; Adornetti, Ines; Ferretti, Francesco; Bassi, Alessia; Colonna, Zaida; De Luca, Vanessa; Canali, Stefano
Abstract : Aim of the present study was to investigate affective and cognitive processes underlying self-narratives of patients with gambling disorder through a verbal language analysis. A semistructured interview was administered to 30 patients with gambling disorder (GD) (24 males and 6 females; mean age: 46.63±9.08) concerning the various thematic areas of their condition: definition of addiction, onset and maintenance of the addiction, relapses, desire, loss of control, control strategies, and treatment. Word usage in the self-narratives was categorized using James Pennebaker's Linguistic Inquiry and Word Count (LIWC) text-analysis software. Specifically, variables analyzed were emotion-related words, the use of pronoun-related words, and tense-related words. The findings showed a higher percentage of negative emotion-related words in the thematic areas of the definition of addiction, maintenance, and loss of control compared with other areas, which may suggest an emotional dysregulation; a higher percentage of first person singular-related words than other person-related words which decreases in the thematic areas of the desire, relapse, and loss of control, which may suggest dissociative phenomena; lastly, a high percentage of present tense-related words, which suggested a static and rigid representation of one's dependency condition in GD patients and a difficulty to self-project into the future. Overall, the linguistic analysis revealed critical issues in affective and cognitive processes in specific phases of addiction in GD patients which could help guide treatment.